Prevalence and exploratory factor analysis of long COVID-19 symptoms among experienced infected population in Bangkok, Thailand - Suphanna Krongthaeo; Suphamas Partiprajak; Noppawan Piaseu; Sineenuch Ckumdee; Chonthicha Taaon; Anon Kongsuwan (BMC, 2024)
Abstract Background Patients with long COVID may experience various concomitant symptoms caused by inflammation, which affect their lives and well-being. In this study, we aimed to (1) investigate the prevalence of long COVID; (2) explore the levels of symptom severity and functional disability owing to long COVID, overall health, and their relationship; and (3) conduct exploratory factor analysis of long COVID-19 symptoms among experienced infected population in the capital of Thailand. Methods A cross-sectional research design was used and a sample of 337 community members with previously COVID-19 infection in Bangkok, Thailand was recruited for this study. Purposive sampling was used. Data collection was performed using an online and a paper-based questionnaire. Descriptive statistics (number, percentage), odds ratio, exploratory factor analysis, and Spearman's rank correlation coefficient were used for the data analysis. Results The prevalence of long COVID was 32.9%. The main reported symptoms included anxiety (28.5%), fatigue (26.1%), and dyspnea (13.4%). There was a significant relationship between symptom severity and functional disability (rs=0.385, p value < 0.01). Overall health was negatively correlated with symptom severity (rs = − 0.291, p < .01) and functional disability (rs = − 0.108, p < .05). Using principal component analysis with Promax rotation, three clusters were identified, explaining 71.44% of the total variance. The Clusters comprised (1) common symptoms of long COVID and communication, (2) fatigue, functioning, and nutritional concerns, and (3) psychosocial impacts. Conclusions The present results might help multidisciplinary care teams understand the concurrent symptoms of patients with long COVID and develop rehabilitation care programs to ease all symptoms simultaneously and improve patients' quality of life.